Association between sarcopenia and nutritional status and physical activity among community‐dwelling Chinese adults aged 60 years and older. Issue 11 (11th February 2017) - Hai, Shan; Cao, Li; Wang, Hui; Zhou, Jianghua; Liu, Ping; Yang, Ying; Hao, Qiukui; Dong, Birong
Aim: Aim: The aim of the present study was to examine the association between sarcopenia and nutritional status and physical activity among community‐dwelling Chinese people aged 60 years and older. Methods: This study was carried out on 836 community‐dwelling Chinese individuals aged ≥60 years to evaluate sarcopenia using the Asian Working Group for Sarcopenia criteria. Sociodemographic characteristics and lifestyle habits were collected using a general questionnaire. Nutritional status was assessed using the Mini Nutritional Assessment and biochemical parameters, whereas physical activity was assessed using the long form of the International Physical Activity Questionnaire. In addition, univariate and multivariate analysis was used to analyze the association between sarcopenia with nutritional status and physical activity. Results: The total prevalence rate of sarcopenia was 10.5%, 47 (11.3%) men and 41 (9.7%) women who were classified as sarcopenia. The prevalence of sarcopenia was significantly lower among the participants of normal nutrition status. Compared with the participants with sarcopenia, those without sarcopenia had higher levels of prealbumin ( P < 0.05) and hemoglobin ( P < 0.05) for both sexes. In the multivariate model, after adjustment for all covariates, the Mini Nutritional Assessment score (adjusted OR 0.769, 95% CI 0.689–0.859, P < 0.05) was statistically significantly associated with sarcopenia, but the relationship between physical activity and sarcopenia was not significant. Conclusions: The prevalence of sarcopenia in the Chinese community‐dwelling population aged 60 years and older was high. There was a significant association between sarcopenia and nutritional status, but not with physical activity, based on a questionnaire. Further studies should evaluate whether maintaining a good nutritional status might be effective in lowering the risk of sarcopenia.Geriatr Gerontol Int 2017; 17: 1959–1966 .